Waqif Preference of Waqf-Based Qardhul Hassan Financing in Malaysia: An Analytic Hierarchy Process Perspective - Amin, Hanudin; Abduh, Muhamad; Shaikh, Imran Mehboob; Panggi, Faizah; Ag Omar, Pg Mohd Faezul Fikri; Rizal, Hamid; Ghazali, Mohd Fahmi; Razak, Dzuljastri Abdul (International Journal of Islamic Economics and Finance (IJIEF), 2023)
Although Islamic banking products like tawarruq and bay al-inah personal financing products available in the Malaysian Islamic banking market, their ability to meet the need of those disadvantaged in the case of health crisis like COVID-19 or financial crisis are somehow marginal.  There is a need for Islamic social finance products to meet this challenge and one of them is the offered qardhul hassan financing funded through crowdfunding on the basis of waqf. This is called waqf-based qardhul hassan financing. For this purpose, this study introduces QAFSCALE, referred to qardhul hassan financing scale to gauge waqif preference on the facility should it is made available in the market. A total of 324 waqif or donors were participated in this study to identify their preference in donating their money in the facility should it is introduced. This study used Attia’s (2010) maqasid al-Shariah theory to generate the QAFSCALE, beginning from the conceptualisations, dimensions and importantly the batter items that represent the QAFSCALE. Analytic Hierarchy Process (AHP) is used. The results obtained indicate that humanity factor is ranked first in importance, followed by family factor, consumer factor and ummah factor. This study limitation is the sample size. A broader sample would have made the result better. Adding to that, the newly designed scale is first of its kind in the context of waqf-based qardhul hassan financing and more studies needed to prove its applicability and generalization, at least. The results obtained might be of interest to managers of Islamic banks and the like to understand their potential waqif preference in the context of waqf-based qardhul hassan financing. Four factors drawn from QAFSCALE were evaluated to identify important factors leading to the waqif contribution on waqf.